IMPACT OF KNOWLEDGE MANAGEMENT IN PRIVATE COLLEGES- AN EMPIRICAL ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
This paper focus on the educational system in private colleges in Kanyakumari District, Tamil Nadu. The concepts of knowledge management are explored and correlated into their dimensions. Empirical analysis is performed to examine the relation between knowledge management prevailing among the educators of private colleges in Kanyakumari District. This study identifies the Knowledge Creation, Knowledge Capture, Knowledge Organization, Knowledge Storage, and Knowledge Dissemination.